Phytol, a diterpene alcohol from chlorophyll, as a drug against neglected tropical disease Schistosomiasis mansoni. - Josué de Moraes; Rosimeire N de Oliveira; Jéssica P Costa; Antonio L G Junior; Damião P de Sousa; Rivelilson M Freitas; Silmara M Allegretti; Pedro L S Pinto (Public Library of Science (PLoS), 2014)
BACKGROUND: Schistosomiasis is a major endemic disease that affects hundreds of millions worldwide. Since the treatment and control of this parasitic disease rely on a single drug, praziquantel, it is imperative that new effective drugs are developed. Here, we report that phytol, a diterpene alcohol from chlorophyll widely used as a food additive and in medicinal fields, possesses promising antischistosomal properties in vitro and in a mouse model of schistosomiasis mansoni. METHODS AND FINDINGS: In vitro, phytol reduced the motor activity of worms, caused their death and confocal laser scanning microscopy analysis showed extensive tegumental alterations in a concentration-dependent manner (50 to 100 µg/mL). Additionally, phytol at sublethal doses (25 µg/mL) reduced the number of Schistosoma mansoni eggs. In vivo, a single dose of phytol (40 mg/kg) administered orally to mice infected with adult S. mansoni resulted in total and female worm burden reductions of 51.2% and 70.3%, respectively. Moreover, phytol reduced the number of eggs in faeces (76.6%) and the frequency of immature eggs (oogram pattern) was significantly reduced. The oogram also showed increases in the proportion of dead eggs. Confocal microcopy studies revealed tegumental damage in adult S. mansoni recovered from mice, especially in female worms. CONCLUSIONS: The significant reduction in parasite burden by this chlorophyll molecule validates phytol as a promising drug and offers the potential of a new direction for chemotherapy of human schistosomiasis. Phytol is a common food additive and nonmutagenic, with satisfactory safety. Thus, phytol has potential as a safe and cost-effective addition to antischistosomal therapy.